To darkness and to death [large type] - Spencer-Fleming, Julia (Thorndike Press, 2014)
Chief of Police Russ Van Alstyne wants nothing more than a quiet day hunting in the mountains on his fiftieth birthday, as his wife plans for the opening gala of the new luxury resort. Reverend Clare Fergusson is getting ready for the bishop's annual visit . . . and one from her long-distance suitor. But in Millers Kill, what begins as a simple case of a woman lost in the woods leads to a tangle of revenge, blackmail, assault, kidnapping, and murder.